Description of the larva of Onthophagus japonicus Harold, 1875 (Coleoptera: Scarabaeidae) from the Russian Far East with a key to the known larvae of the genus - S.A. Shabalin (Кавказский энтомологический бюллетень, 2018)
A larva of the Onthophagus japonicus Harold, 1875 is described and illustrated for the first time from the south of Primorskiy Region, Russia. The larva of O.  japonicus is similar to that of O.  fodiens Waterhouse, 1875 and O. gibbulus (Pallas, 1781) by median part of anal sternite without palidium, but differs from the former by epicranium with 3–4  dorsoepicranial setae (6–10  in O.  fodiens); from the latter by maxillary stridulatory area with 4 anterior setae (dorsal view) (6–8 in O. gibbulus), by galea with 11 lateral setae ventrally (14–18 in O. gibbulus). A key to the known larvae of six species (from 14 species occurring the Russian Far East) of the genus Onthophagus Latreille, 1802 is given.